Chemical Variant of 7-deaza-dGTP for Improved GC-rich PCR and Amplification - Paul, Natasha (Association of Biomolecular Resource Facilities, 2013)
PCR amplification of nucleic acids is a fundamental technique used in many molecular biology laboratories. Despite its widespread use, GC-rich regions of DNA sequence remain a challenge for amplification. Sequences high in GC content can form strong secondary structure, which prevents strand denaturation and blocks processive DNA polymerase amplification. As a consequence, mis-priming is prominent and can complicate specific product formation. Especially as applied to the molecular diagnosis of inheritable diseases, several assay modifications have been developed to improve the specificity of target amplification. These approaches include specialized polymerases, Hot Start assays, addition of organic molecules, and thermal cycling alterations. However, as the GC content increases, the combination of two or three approaches may be required. Here, we show how 7-deaza-dGTP, a commonly used molecule to amplify GC-rich targets, can highly improve results when a thermolabile protecting group is incorporated at the 3′-hydroxyl. The presence of the protecting group blocks low temperature primer extension and only allows nucleotide incorporation at higher temperatures when the protecting group is removed, improving PCR specificity as a result. Amplification specificity of GC-rich targets is further improved when a Hot Start version of all dNTPs are employed. This 7-deaza-dGTP containing Hot Start mixture allows for challenging targets of more than 85% GC content, such as Fragile X, to be amplified. Another benefit of this technology is in downstream sequencing reactions. PCR amplification of problematic targets with a Hot Start 7-deaza-dGTP mix prior to Sanger dideoxy sequencing can significantly improve the read quality along the entire sequence. In summary, the use of dNTPs modified with thermolabile chemistry simplifies GC-rich amplification and provides a valuable solution that can improve disease diagnosis.